Civil-Military Cooperation in Strengthening the National Airspace Security System - Soleman Koloay, Jorry; Arinanto, Satya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Weak coordination and communication, the existence of sectoral egos between agencies, and the tendency to act individually without integrated action resulted in the cohesiveness and speed of state handling responses to various threats and violations of airspace to be weak which ultimately affected the condition of national resilience. The concept of civil-military cooperation to strengthen the national airspace security system is built through the formulation of the National Airspace Management Bill, the establishment of institutions that accommodate coordination and cooperation between civil-military agencies, and the appointment of a command-and-control center that integrates and harmonizes the operations of all agencies. This study uses a qualitative approach with a narrative qualitative analysis method, to discuss theory, review policies and analyze expert opinions on the need for civil-military cooperation to strengthen the national airspace security system, to then draw conclusions and recommendations. This study is expected to be useful for efforts to formulate national airspace management policies that are very strategic and needed.